Efforts to Improve Learning Outcomes in Theme 3 Sub-theme 3 by Using Cooperative Learning Learning Strategies - Tri Widiyanti (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
The purpose of this study was to improve student learning outcomes on theme 3 sub-theme 3 in grade III elementary schools with cooperative learning strategies. The research conducted was a Classroom Action Research (CAR) in three cycles, with each cycle consisting of one meeting. The stages of each cycle are planning, implementing, observing and reflecting. Each meeting is conducted with a formative test to determine the development of students. In the first cycle students who completed after carrying out the formative test were 53.1%. In cycle II students who completed after carrying out the formative test were 81.25%. In the third cycle students who completed after carrying out the formative test were 87.5%. These results indicate that the cooperative learning strategy can improve student learning outcomes, especially the subject matter of the theme 3 sub-themes 3 Class III at Wijayakusuma Private Elementary School.